Farid Study and Tahir Tounsvi - Perveen, Fauzia; Arif, Muhammad; Saleem, Muhammad (sourcecoder, 2023)
Khawaja Ghulam Farid is considered is the last sufi poet of Saraiki language. The unity of existence, the love of guide and the views of nature are the special themes of his poetry. Khawaja Ghulam Farid is an eminent poet. Many researchers and critics have worked on his life and poetry. One prominent figure among them is Tahir Tounsvi . Due to being Saraiki, Tahir Tounsvi has made significant efforts to understand and explain Farid’s thoughts. This article encompasses those aspects and subjects that have come to the light through Tahir Tounsvi’s research regarding Khawaja Farid.